Diverse roles of the CIPK gene family in transcription regulation and various biotic and abiotic stresses: A literature review and bibliometric study - Yang, Chen; Yi-feng, Jin; Yushu, Wang; Yansong, Gao; Qi, Wang; Xue, You (Frontiers in Genetics, 2022)
CIPKs are a subclass of serine/threonine (Ser/Thr) protein kinases. CBLs are ubiquitous Ca2+ sensors that interact with CIPK with the aid of secondary Ca2+ messengers for regulation of growth and development and response to stresses faced by plants. The divergent roles of the CIPK-CBL interaction in plants include responding to environmental stresses (salt, cold, drought, pH, ABA signaling, and ion toxicity), ion homeostasis (K+, NH4+, NO3−, and microelement homeostasis), biotic stress, and plant development. Each member of this gene family produces distinct proteins that help plants adapt to diverse stresses or stimuli by interacting with calcium ion signals. CIPK consists of two structural domains—an N-terminal domain and a C-terminal domain—connected by a junction domain. The N-terminal domain, the site of phosphorylation, is also called the activation domain and kinase domain. The C-terminal, also known as the regulatory domain of CIPK, further comprises NAF/FISL and PPI. CBL comprises four EF domains and conserved PFPF motifs and is the site of binding with the NAF/FISL domain of CIPK to form a CBL-CIPK complex. In addition, we also performed a bibliometric analysis of the CIPK gene family of data extracted from the WoSCC. A total of 95 documents were retrieved, which had been published by 47 sources. The production over time was zigzagged. The top key terms were gene, CIPK, abiotic stress, and gene expression. Beijing Forestry University was the top affiliation, while The Plant Cell was the top source. The genomics and metabolomics of this gene family require more study.